Histone H3.3 K27M Accelerates Spontaneous Brainstem Glioma and Drives Restricted Changes in Bivalent Gene Expression - Larson, Jon D; Kasper, Lawryn H; Paugh, Barbara S; Jin, Hongjian; Wu, Gang; Kwon, Chang-Hyuk; Fan, Yiping; Shaw, Timothy I; Silveira, André B; Qu, Chunxu; Xu, Raymond; Zhu, Xiaoyan; et al. (Cancer cell, 2019)
Diffuse intrinsic pontine gliomas (DIPGs) are incurable childhood brainstem tumors with frequent histone H3 K27M mutations and recurrent alterations in PDGFRA and TP53. We generated genetically engineered inducible mice and showed that H3.3 K27M enhanced neural stem cell self-renewal while preserving regional identity. Neonatal induction of H3.3 K27M cooperated with activating platelet-derived growth factor receptor α (PDGFRα) mutant and Trp53 loss to accelerate development of diffuse brainstem gliomas that recapitulated human DIPG gene expression signatures and showed global changes in H3K27 posttranslational modifications, but relatively restricted gene expression changes. Genes upregulated in H3.3 K27M tumors were enriched for those associated with neural development where H3K27me3 loss released the poised state of apparently bivalent promoters, whereas downregulated genes were enriched for those encoding homeodomain transcription factors.